2009
DOI: 10.1093/ndt/gfp704
|View full text |Cite
|
Sign up to set email alerts
|

Dosing of daptomycin in intensive care unit patients with acute kidney injury undergoing extended dialysis--a pharmacokinetic study

Abstract: Our data suggest that patients treated with ED using a high-flux dialyzer (polysulphone, 1.3 m(2); blood and dialysate flow, 160 ml/min; ED time, 480 min) and employing current dosing regimen, 6 mg/kg daptomycin every 48 h, run the risk of becoming significantly under dosed if one adheres to a twice daily dosing schedule that is recommended for patients on maintenance haemodialysis. Our data suggest that a daily dose of 6 mg/kg daptomycin is necessary in this special patient population to avoid under dosing, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…The present study suggests that ampicillin/sulbactam should be given 3 hours before ED (7). However, these same researchers recently studied daptomycin and a similar ED regimen, and they recommended that daptomycin administration should occur within 8 hours of ED (22). Gentamicin has been studied in ED, and the study suggested dosing immediately after ED (23).…”
mentioning
confidence: 78%
“…The present study suggests that ampicillin/sulbactam should be given 3 hours before ED (7). However, these same researchers recently studied daptomycin and a similar ED regimen, and they recommended that daptomycin administration should occur within 8 hours of ED (22). Gentamicin has been studied in ED, and the study suggested dosing immediately after ED (23).…”
mentioning
confidence: 78%
“…However, insufficient concentrations will result if the dose is administered during rather than after the dialysis treatment (44). In patients in intensive care, those undergoing extended dialysis should receive 6 mg/kg once daily to prevent suboptimal drug exposure, whereas those on continuous venovenous hemodialysis should receive 8 mg/kg every 48 h (45,46).…”
Section: Daptomycin Pharmacokineticsmentioning
confidence: 99%
“…Ampicillin/ sulbactam (2 g/1 g) was infused intravenously in 12 patients over a period of 30 minutes using an infusion pump. ED was performed using the Genius batch dialysis system (Fresenius Medical Care, Bad Homburg, Germany) with a polysulfone high-flux dialyzer (F60S; surface area, 1.3 m 2 ) (Fresenius Medical Care) as described previously (12). The technical details of the system are explained elsewhere (17).…”
Section: Methodsmentioning
confidence: 99%
“…For the collection of the predialyzer and postdialyzer samples, ultrafiltration was stopped. Furthermore, in seven patients we took samples from the total spent dialysate after it was mixed by air insufflations as well as from the total collected ultrafiltrate, as described previously (12).…”
Section: Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation